Postharvest behavior of cape gooseberry Physalis peruviana L. fruit under different storage temperatures - Pinzón, Elberth Hernando; Reyes, Andrea Johana; Álvarez-Herrera, Javier Giovanni; Leguizamo, María Fernanda; Joya, José Gregorio (Revista de Ciencias Agrícolas, 2015)
considerably their postharvest life. Therefore, we have developed different techniques to delay the ripening processes. These included atmospheric modification or storage at different temperatures; the latter is widely used due to its ease handling and low cost. Thus, the behavior of cape goose berry fruit, ecotype ‘Colombia’, was evaluated under different storage temperatures, through assessment of fresh mass loss, color index, firmness, total soluble solids, and total acidity. Significant differences were observed, for all variables, between treatments under refrigeration and the control. Storage temperature satisfactorily influenced all physical and chemical  characteristics assessed. After 18 days of storage, the refrigerated fruits retain their quality and were, thus, favorable for marketing. However, we hope in future studies assess shelf life